Social justice leadership in multicultural schools: the case of an ethnically divided society. Issue 1 (2nd January 2017) - Zembylas, Michalinos; Iasonos, Sotiroula
Abstract : This paper reports on the results of an exploratory study focusing on the perceptions of elementary school principals who espouse a critical multicultural approach and show signs of a social justice leadership style. The study has taken place in an ethnically divided society (Cyprus) in which the political situation seems to influence the ways in which school leaders perceive issues of justice and multiculturalism. Semi-structured, in-depth interviews were conducted with 10 principals who espoused a critical multicultural approach and subscribed to values of social justice leadership. The analysis of these principals' interviews reveals two important findings—one concerning the conceptualization of critical multiculturalism in a society that suffers from ethnic division and the other concerning the contextualization of social justice leadership in this setting. The paper discusses the implications for leadership preparation programmes and for future research on social justice leadership and critical multiculturalism.